2019
DOI: 10.26434/chemrxiv.7882799.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Integrated Console for Capsule-Based, Fully Automated Organic Synthesis

Abstract: The current laboratory-based practice of organic synthesis renders automation difficult, suffers from safety and environmental hazards, and hampers the implementation of artificial intelligence guided drug discovery. Using a combination of innovative reagent design, hardware engineering, and a simple operating system we provide an instrument capable of executing complex organic reactions with prepacked capsules in a fully automated fashion. The machine conducts coupling reactions and delivers the purified prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Challenge:A utomate the planning of multistep chemical syntheses Many discovery tasks involve proposing new chemical matter; approaching these tasks with autonomous systems requires the ability to synthesize novel compounds on-demand. [184] Ap articularly challenging class of experiments is ondemand synthesis.T he primary methodological challenge for general-purpose automated synthesis is the planning of processes-designing multistep synthetic routes using available building blocks;s electing conditions for each reaction step including quantities,t emperature,a nd time;a nd automating intermediate and final purifications.I fr educed to stirring, heating, and fluid transfer operations,c hemical syntheses are straightforward to automate, [186][187][188] and existing robotic platforms (Figure 3) can execute as eries of process steps if those steps are precisely planned. [184,189] However, current computer-aided synthesis planning (CASP) tools are unable to make directly implementable recommendations with this level of precision.…”
Section: Experimental Validationmentioning
confidence: 99%
“…Challenge:A utomate the planning of multistep chemical syntheses Many discovery tasks involve proposing new chemical matter; approaching these tasks with autonomous systems requires the ability to synthesize novel compounds on-demand. [184] Ap articularly challenging class of experiments is ondemand synthesis.T he primary methodological challenge for general-purpose automated synthesis is the planning of processes-designing multistep synthetic routes using available building blocks;s electing conditions for each reaction step including quantities,t emperature,a nd time;a nd automating intermediate and final purifications.I fr educed to stirring, heating, and fluid transfer operations,c hemical syntheses are straightforward to automate, [186][187][188] and existing robotic platforms (Figure 3) can execute as eries of process steps if those steps are precisely planned. [184,189] However, current computer-aided synthesis planning (CASP) tools are unable to make directly implementable recommendations with this level of precision.…”
Section: Experimental Validationmentioning
confidence: 99%
“…This form of "synthesis discretization" may permit one to rein in the exponentially high permutations that arise from a non-bounded parameter space and reduce the cost of engineered solutions. More recently a group at ETH Zurich (Jiang et al, 2019) have shown how innovative reagent design, custom hardware engineering, and a precisely executed workflow can lead to complete and repeatable workflows that lead to cleanly isolated products. In all likelihood reagent formulation will play an everincreasing role in the development and expansion of practical automated synthetic solutions.…”
Section: Reagent Delivery Strategiesmentioning
confidence: 99%
“…Product isolation often possesses the greatest challenge in providing robust automated processes. As shown in apparatus developed by scientists at ETH Zurich mentioned earlier (Jiang et al, 2019), special considerations for product isolation are likely just as important as the reaction setup itself if improved automated outcomes are desired. Confounding factors include the largely unpredictable physical characteristics of the raw reaction mixtures.…”
Section: Product Isolationmentioning
confidence: 99%
“…Synthesen nach Bedarf (On-Demand-Synthesen) stellen eine besonders anspruchsvolle Klasse von Experimenten dar. Bei automatischen Mehrzwecksynthesen liegt die grçßte methodische Herausforderung in der Prozessplanung -also in der Entwicklung von mehrstufigen Syntheserouten mit verfügbaren Bausteinen, der Auswahl der Bedingungen fürjeden Reaktionsschritt einschließlich Mengen, Te mperatur und Reaktionszeit sowie der automatischen Zwischen-und Endreinigung.S ofern es nur um das Rühren, Erwärmen und Überführen von Flüssigkeiten geht, sind chemische Synthesen leicht zu automatisieren, [186][187][188] und bestehende Automaten (Abbildung 3) kçnnen bei genauer Planung mehrere Prozessschritte nacheinander ausführen. [184,189] Die derzeitigen "Computer-Aided Synthesis Planning"(CASP)-Programme sind jedoch nicht in der Lage,a uf diesem Präzisionsniveau Empfehlungen zu geben, die direkt implementierbar sind.…”
Section: Angewandte Chemieunclassified